Entrepreneurship Counseling Seminar, Basic, Bookkeeping Management Training For SMEs, And A Cooking Competition For PKK Women In Mojoasem Village Kec. Sidayu - Sari, Rafika; Meiriasari, Vhika (Dinasti Publisher, 2024)
From January 19 to April 15, 2018, Muhammadiyah Gresik University hosted the Real Work Lecture (KKN) for 2018. The Mojoasem Village in the Sidayu District of the Gresik Regency was one of the locations where KKN operations were conducted. Students in the accounting studies program participate in excellent employment programs, such as the Basic Bookkeeping Management Training at UKM and the Mojoasem Village Cooking Competition and Entrepreneurship Counseling Seminar for PKK Women. A company unit's financial transactions are recorded, grouped, and summarized to create financial reports. Leverage money may be viewed as a management tool for businesses when making decisions. External parties can also determine the state and working hours of a business unit based on the relevant exchange rate laporan. Laporan keuagan walau hanya pembukuan sederhana pada usaha kecil menengah (UKM), terapat penting di suatu unit usaha. During this time, we also have other work programs. Nevertheless, many of the pendampingan pembukuan Desa Mojoasem activities aim to support UKM employees in their motivation and to help them manage their finances in a way that is fair and compliant with established standards of accountability. In order to complete this task, Mojoasem Village will receive an introduction of basic accounting bookkeeping and financial management practices. In order to encourage innovation and increase PKK women's excitement for successful enterprise, we also run culinary competitions and counseling on entrepreneurship workshops. The students in the study program for accounting executed the scheduled tasks with efficiency and success. Everyone involved hopes that this project will assist Mojoasem Village become even better, particularly in the village's economy. As accounting students at Muhammadiyah University of Gresik's Faculty of Economics & Business, we are supported by students from different majors into one 4 Thematic KKN Group Team with the hopes that Mojoasem Village will get better.